Clinical outcomes of robot-assisted vs. conventional free-hand technique in spine surgery - Yan, Hui; Wu, Yuxuan; Cheng, Xiaokang; Xu, Chunyang; Yang, Tianci; Bao, Beixi (Frontiers in Surgery, 2025)
BackgroundRobot-assisted surgery has been increasingly applied in spinal surgery in recent years, but the differences in efficacy compared to conventional free-hand surgery remain unclear. This study aims to evaluate the impact of these two surgical approaches on spinal surgery patients by analyzing baseline characteristics, surgical data, short-term postoperative outcomes, and long-term functional recovery and pain relief.MethodsThis study first analyzed the differences in baseline characteristics and surgical data between the robot-assisted and conventional free-hand surgery groups, including age, gender, diabetes, hypertension, smoking, and alcohol consumption. Multivariate logistic regression was then used to explore the effects of baseline characteristics and surgical methods on short-term postoperative outcomes, such as complications, reoperations, fracture healing, and spinal alignment recovery. Finally, generalized estimating equations (GEE) were employed to assess the impact of surgical methods on long-term postoperative outcomes, including Oswestry Disability Index (ODI) and pain scores.ResultsDiabetes and hypertension significantly increased the risk of postoperative complications and reoperation, while robot-assisted surgery significantly reduced the incidence of complications and reoperation. In terms of spinal structural recovery after surgery, the robot-assisted surgery group showed better results. Long-term follow-up revealed that robot-assisted surgery significantly reduced ODI and pain scores, and over time, the robot-assisted group consistently demonstrated superior functional recovery and pain relief compared to the conventional surgery group.ConclusionRobot-assisted surgery showed significant advantages in both short-term postoperative recovery and long-term functional improvement and pain relief. It outperformed conventional free-hand surgery in reducing complication rates, accelerating postoperative recovery, lowering reoperation rates, and promoting fracture healing and spinal alignment recovery.